The Potential the Baruasa of Brown Sugar as a traditional cake through the use of rice shards - Rouw, Randy Frank; Wijaya, Hengki (Sekolah Tinggi Teologi Levinus Rumaseb Sentani, Papua, 2024)
This paper aims to determine the processing of Baruasa made from rice flakes and palm sugar. Brown sugar is a brown sweetener—made from palm sugar by boiling palm sap water. This material can be used as an ingredient for making traditional Baruasa brown sugar cakes. Qualitative research methods with data collection techniques through literature review, interviews and field observations. The result of this research shows that the potential for developing traditional cakes with natural raw materials and natural dyes and the utilization of rice shards from factories can benefit small and home industries.